2016
DOI: 10.1186/s12920-016-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

A 19-Gene expression signature as a predictor of survival in colorectal cancer

Abstract: BackgroundHistopathological assessment has a low potential to predict clinical outcome in patients with the same stage of colorectal cancer. More specific and sensitive biomarkers to determine patients’ survival are needed. We aimed to determine gene expression signatures as reliable prognostic marker that could predict survival of colorectal cancer patients with Dukes’ B and C.MethodsWe examined microarray gene expression profiles of 78 archived tissues of patients with Dukes’ B and C using the Illumina DASL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Using a newly developed monoclonal antibody against DUOX2, increased immunohistochemical staining was observed in various tumor types, including prostate, lung, breast, and colon [109]. These observations suggest that DUOX2-derived H 2 O 2 plays an important role in carcinogenesis and tumor progression, which is supported by a recent report demonstrating that DUOX2 upregulation in colorectal cancer correlates with poor prognosis[110]. Analysis of data available from the NIH funded Tissue Cancer Genome Atlas Project (TCGA) (http://cancergenome.nih.gov/) further confirms that DUOX2 is overexpressed especially in colon and esophageal cancers, although expression levels are highly variable and DUOX2 is not significantly altered in other cancers (Fig.…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 82%
“…Using a newly developed monoclonal antibody against DUOX2, increased immunohistochemical staining was observed in various tumor types, including prostate, lung, breast, and colon [109]. These observations suggest that DUOX2-derived H 2 O 2 plays an important role in carcinogenesis and tumor progression, which is supported by a recent report demonstrating that DUOX2 upregulation in colorectal cancer correlates with poor prognosis[110]. Analysis of data available from the NIH funded Tissue Cancer Genome Atlas Project (TCGA) (http://cancergenome.nih.gov/) further confirms that DUOX2 is overexpressed especially in colon and esophageal cancers, although expression levels are highly variable and DUOX2 is not significantly altered in other cancers (Fig.…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 82%
“…For example, increase of total plasma ceramide in the patients undergoing radiation therapy in combination with irinotecan chemotherapy was associated with favorable tumor response (Dubois et al, 2016). Analogously, CerS6 was identified as a member of the 19-gene-signature predicting survival of patients with colorectal cancer (Abdul Aziz et al, 2016). Mechanistic basis for the distinct functions of endogenous ceramides is not known; however, interaction of ceramides with specific proteins was suggested to be responsible for this, at least in part (Saddoughi et al, 2013).…”
Section: Ceramide and Cancermentioning
confidence: 99%
“…The most wildly recognized prognostic biomarkers for immune therapy were programmed death ligand (PD-1), tumor mutation burden (TMB) and microsatellite instability/ mismatch repair de ciency (dMMR) 14 . However, throughout research, these solitary biomarkers only showed moderate strati cation e cacy [15][16][17][18] , more so in CRC 19 , and a universal immune-related gene (IRG) panel as prognostic signature in CRC has not been scored Within the decade, several limited-scale studies have made attempts developing predictive gene signature to stratify high-risk population with high-throughput technology [20][21][22] . However, most suffer from overtting due to insu cient sample pool, and an external validation is hardly presented.…”
Section: Introductionmentioning
confidence: 99%